Persepsi Siswa tentang Kompetensi Profesional Guru di SMK Negeri 1 Sijunjung - Bulara, Adinkga Rahma; Ermita, Ermita (Lembaga Yasin AlSys, 2025)
This study was motivated by field findings at SMK Negeri 1 Sijunjung, which indicated that teachers' professional competence had not yet reached optimal levels. The aim of this research is to obtain information regarding teachers’ professional competence from students’ perspectives, focusing on their ability to master teaching materials, apply instructional methods, manage and use learning media, and conduct learning assessments. A descriptive quantitative approach was employed, with the population consisting of all 389 eleventh-grade students. A sample of 80 students was selected using proportional simple random sampling. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability, resulting in 41 valid and reliable items. Data were analyzed using the mean formula. The results show that students’ perceptions of teachers’ professional competence fall into the